The material and human basis used in tourism and agrotourism in Tulcea County - Eugenia-Dorina Ciobanu; Raluca Alexandra Necula (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The present article aims to identify, analyze and present the evolution, in recent years, of the technical-material and human basis used in the tourism and agrotourism in Tulcea County. In order to do that, the following indicators have been used in the analysis: the evolution of the tourism and agrotourism boardings from Tulcea County, the evolution of the tourist accommodation structures with lodging functions - from the rural area -Tulcea County, the evolution of the accommodation capacity, the evolution of the civil population sorted by national economy activities - Tulcea County, the evolution of the average number of employees sorted by national economy activities - Tulcea County and the evolution of the average number of employees from hotels and restaurants - Tulcea County. At the end of this analysis, we can conclude that the technical-material and human basis used in the tourism and agrotourism activity in Tulcea county is there, but is underdeveloped compared to the touristic potential of the area, that is not capitalized to its maximum capacity in the tourism and agrotourism activity.
Keywords: L83; 330; tourism; agroturism; Tulcea